Proximal Femur Volumetric Bone Mineral Density and Mortality: 13 Years of Follow‐Up of the AGES‐Reykjavik Study - Marques, Elisa A; Elbejjani, Martine; Gudnason, Vilmundur; Sigurdsson, Gunnar; Lang, Thomas; Sigurdsson, Sigurdur; Aspelund, Thor; Meirelles, Osorio; Siggeirsdottir, Kristin; Launer, Lenore; Eiriksdottir, Gudny; Harris, Tamara B (Journal of bone and mineral research, 2017)
ABSTRACT Bone mineral density (BMD) has been linked to mortality, but little is known about the independent contribution of each endosteal bone compartment and also the rate of bone loss to risk of mortality. We examined the relationships between (1) baseline trabecular and cortical volumetric BMD (vBMD) at the proximal femur, and (2) the rate of trabecular and cortical bone loss and all‐cause mortality in older adults from the AGES‐Reykjavik study. The analysis of trabecular and cortical vBMD and mortality was based on the baseline cohort of 4654 participants (aged ≥66 years) with a median follow‐up of 9.4 years; the association between rate of bone loss and mortality was based on 2653 participants with bone loss data (median follow‐up of 5.6 years). Analyses employed multivariable Cox‐proportional models to estimate hazard ratios (HRs) with time‐varying fracture status; trabecular and cortical variables were included together in all models. Adjusted for important confounders, Cox models showed that participants in the lowest quartile of trabecular vBMD had an increased risk of mortality compared to participants in other quartiles (HR = 1.12; 95% confidence interval (CI), 1.01 to 1.25); baseline cortical vBMD was not related to mortality (HR = 1.08; 95% CI, 0.97 to 1.20). After adjustment for time‐dependent fracture status, results were attenuated and not statistically significant. A faster loss (quartile 1 versus quartiles 2–4) in both trabecular and cortical bone was associated with higher mortality risk (HR = 1.37 and 1.33, respectively); these associations were independent of major potential confounders including time‐dependent incident fractures (HR = 1.32 and 1.34, respectively). Overall, data suggest that faster bone losses over time in both the trabecular and cortical bone compartments are associated with mortality risk and that measurements of change in bone health may be more informative than single‐point measurements in explaining mortality differences in older adults. © 2017 American Society for Bone and Mineral Research.